Fisheries Subsidies under International Law - Chen, Chen-Ju.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Subsidies to fisheries have been in existence for centuries. However, these remained outside the spotlight of the international community until the turn of this century when the negative effects that fisheries subsidies have on international trade, the environment and sustainable development became increasingly clear. As a result the Doha Round Negotiations set the parameters for an effective fisheries subsidies regime. WTO Members thus embarked in intensive negotiations with the collaboration of various international organizations. These negotiations culminated with publication of the legal text of the Chairman of the Negotiating Group on Rules in 2007 which reflects to a large extent the mandates of the Ministerial Conferences and reconciles the diverse interests of the negotiators. The EU as a major WTO Member and with its own Common Fisheries Policy which has been in effect for a number of years can serve as the basis for comparison and improvement of the proposed regulations.
1: Fisheries Subsidies and Current Regulations under International Law -- 2: Fisheries Subsidies Negotiations within the WTO Framework -- 3: Analysis of the Proposed Fisheries Subsidies Regulations by the Chairman of the WTO Negotiating Group on Rules -- 4: Regulations of Fisheries Subsidies under the European Union Regime and Comparison with the Fisheries Subsidies Regulations in the WTO Chair$1 (Bs Text -- Conclusion.s
Keywords: Law; Comparative law; Public law; Law; International & Foreign Law/Comparative Law; European Law/Public International Law; Public Law